UVA-Triggered Drug Release and Photo-Protection of Skin - Karisma, Vega Widya; Wu, Wei; Lei, Mingxing; Liu, Huawen; Nisar, Muhammad Farrukh; Lloyd, Matthew D.; Pourzand, Charareh; Zhong, Julia Li (Frontiers in Cell and Developmental Biology, 2021)
Light has attracted special attention as a stimulus for triggered drug delivery systems (DDS) due to its intrinsic features of being spatially and temporally tunable. Ultraviolet A (UVA) radiation has recently been used as a source of external light stimuli to control the release of drugs using a “switch on- switch off” procedure. This review discusses the promising potential of UVA radiation as the light source of choice for photo-controlled drug release from a range of photo-responsive and photolabile nanostructures via photo-isomerization, photo-cleavage, photo-crosslinking and photo-induced rearrangement. In addition to its clinical use, we will also provide here an overview of the recent UVA-responsive drug release approaches that are developed for phototherapy and skin photoprotection.